2020
DOI: 10.1007/jhep01(2020)028
|View full text |Cite
|
Sign up to set email alerts
|

Exotic lepton-flavor violating Higgs decays

Abstract: Exotic Higgs decays are promising channels to discover new physics in the near future. We present a simple model with a new light scalar that couples to the Standard Model through a charged lepton-flavor violating interaction. This can yield exciting new signatures, such as h → e + e + µ − µ − , that currently have no dedicated searches at the Large Hadron Collider. We discuss this model in detail, assess sensitivity from flavor constraints, explore current constraints from existing multi-lepton searches, and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 122 publications
(159 reference statements)
1
11
1
Order By: Relevance
“…Also, our results are slightly severer than those in refs. [60,61]. 9 The same conclusion was made in ref.…”
Section: Collider Signals At Belle IIsupporting
confidence: 83%
See 2 more Smart Citations
“…Also, our results are slightly severer than those in refs. [60,61]. 9 The same conclusion was made in ref.…”
Section: Collider Signals At Belle IIsupporting
confidence: 83%
“…(3.1) and (3.2), the transition of the muonium into antimuonium does not proceed via the scalar. Hence, the flavor-violating complex scalar can explain both g − 2 anomalies simultaneously, though the UV completion is nontrivial [61]. 18,19 At the Belle II experiment, the measurement of the forward-backward asymmetry could probe such a parameter region when m S > O(1) GeV; the muon g − 2 discrepancy requires larger couplings, which enhance A FB , too.…”
Section: Jhep06(2020)040mentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, when the mass is below O(10) GeV, it is rather difficult to search for such new particles at the LHC typically due to the limitation of the lepton detection for their transverse momentum is smaller than 10-20 GeV [33,34]. For instance, it is explicitly shown that the LHC is only sensitive down to m X = 10 GeV for such LFV particles [29,35,36]. Figure 2 summarizes the current allowed and the future testable JHEP09(2020)144 Figure 2.…”
Section: Jhep09(2020)144mentioning
confidence: 99%
“…#14 Recently, LHC sensitivities to the flavor-violating ALP were studied by Ref. [58] in a process of pp → h → µ ± µ ± e ∓ e ∓ . It was shown that the region of 20 m a 80 GeV can be probed accurately and its e + e !…”
Section: 1mentioning
confidence: 99%